The Relationship Between the Age of Toddlers, the Provision of Formula Milk, and Residence Location with the Occurrence of Diarrhoea: An Analysis of DHS Data - Achmad Dzulkifli; Sri Sumarmi; Emyr Reisha Isaura; Achidah Nur Syahdana; Trias Mahmudiono; Mahmudah Mahmudah; RR Soenarnatalina Melaniani (Amerta Nutrition)
Background: Approximately 16% of mortality in children under five years old is associated with diarrhoea. In Ghana, diarrhoea is the third most common cause of death among infants. Ghana is one of the countries in Africa with an estimated 1,700 deaths due to diarrhoea in infants.